STANDAR KUALIFIKASI DAN KOMPOTENSI KEPEMIMPINAN KEPALA SEKOLAH - Jufri Dolong, M. (Universitas Islam Negeri Alauddin Makassar, 2019)
Qualification standards and the potential of the School Principal as an educational leader responsible for the continuous growth of teachers, he must be able to help teachers recognize the needs of the community, assist teachers in fostering the curriculum, the needs and abilities of students. He must be able to stimulate teachers to develop teaching methods and procedures. Able to help evaluate educational programs and student learning outcomes, in addition to that the principal must also be able to assess the nature and ability of teachers, so that they can be improved. To be able to carry out these responsibilities, the principal must have the education and experience needed for an educational leader. The principal function of the principal as a leader is to create a learning situation so that teachers can teach and students can learn well. In carrying out this function, the principal has a dual responsibility of carrying out the administration of the school so as to create a good teaching and learning process, and carrying out supervision so that the ability of teachers increases in guiding the growth of their students